2022
DOI: 10.1111/bre.12728
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic record of continental breakup, offshore NW Australia—Discussion

Abstract: Reeve et al. (2022) address the stratigraphic record of continental breakup by focusing on a set of stratigraphic unconformities from a proxima l sector of the NW Australian continenta l margin, inboard from the Exmouth Plateau. They suggest that such unconfor mities can potentially document a well-defined three-stage process: end of the synrift phase, formatio n of a wide continent-ocea n transitio n zone (COTZ) and generatio n of 'true' Penrose-type oceanic crust. We counterargue that continental breakup is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
3
10
1
Order By: Relevance
“…From these findings, we suggested that the three unconformities may have formed in response to (1) localisation of magma‐assisted rifting, linked to COTZ development and/or seafloor spreading, between 134.98 and 133.74 Ma (Intra‐Valanginian Unconformity); (2) generation of magmatic crust in COTZs between ~134 and 133 Ma (Top Valanginian Unconformity); and (3) full continental lithospheric breakup between ~132.5 and 131 Ma (Intra‐Hauterivian Unconformity) (Reeve et al, 2022). Note that contrary to the claim made by Alves et al (2022), we did not suggest that the end of the syn‐rift phase was defined by the formation of a single unconformity. Instead, we recognised that breakup was “represented by multiple unconformities [and inherently the surrounding strata] reflecting a complex history of uplift and subsidence during the transition from continental rifting to seafloor spreading” (Reeve et al, 2022).…”
Section: Summary Of Reeve Et Al (2022)contrasting
confidence: 99%
See 4 more Smart Citations
“…From these findings, we suggested that the three unconformities may have formed in response to (1) localisation of magma‐assisted rifting, linked to COTZ development and/or seafloor spreading, between 134.98 and 133.74 Ma (Intra‐Valanginian Unconformity); (2) generation of magmatic crust in COTZs between ~134 and 133 Ma (Top Valanginian Unconformity); and (3) full continental lithospheric breakup between ~132.5 and 131 Ma (Intra‐Hauterivian Unconformity) (Reeve et al, 2022). Note that contrary to the claim made by Alves et al (2022), we did not suggest that the end of the syn‐rift phase was defined by the formation of a single unconformity. Instead, we recognised that breakup was “represented by multiple unconformities [and inherently the surrounding strata] reflecting a complex history of uplift and subsidence during the transition from continental rifting to seafloor spreading” (Reeve et al, 2022).…”
Section: Summary Of Reeve Et Al (2022)contrasting
confidence: 99%
“…We agree with Alves et al (2022) that lithospheric breakup in the Argo Abyssal Plain may also have instigated formation of a substantially older, margin‐wide unconformity in the Oxfordian, although exploring this was beyond the scope of Reeve et al (2022). Our interpretation that the Intra‐Valanginian Unconformity formed due to localisation of magma‐assisted rifting (Reeve et al, 2022) is also consistent with the suggestion of Alves et al (2022) that it marks lithospheric breakup in the Cuvier Abyssal Plain.…”
Section: Proposed Continental Breakup Events Offshore Nw Australiasupporting
confidence: 91%
See 3 more Smart Citations